Antibiotic mediated synthesis of gold nanoparticles with potent antimicrobial activity and their application in antimicrobial coatings - Rai, Akhilesh; Prabhune, Asmita; Perry, Carole C. (Journal of Materials Chemistry, 2010)
We report a one-pot synthesis of spherical gold nanoparticles (52-22 nm) and their capping with cefaclor, a second-generation antibiotic, without use of other chemicals. The differently sized gold nanoparticles were fabricated by controlling the rate of reduction of gold ions in aqueous solution by varying the reaction temperature (20-70 degrees C). The primary amine group of cefaclor acted as both the reducing and capping agent for the synthesis of gold nanoparticles leaving the beta-lactam ring of cefaclor available for activity against microbes. Antimicrobial testing showed that cefaclor reduced gold nanoparticles have potent antimicrobial activity against both Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria as compared to cefaclor or gold nanoparticles alone. The minimum inhibition concentrations (MICs) of cefaclor reduced gold nanoparticles were 10 mu g mL(-1) and 100 mu g mL(-1) for S. aureus and E. coli respectively. The cefaclor reduced gold nanoparticles were further coated onto poly(ethyleneimine) (PEI) modified glass surfaces to obtain antimicrobial coatings suitable for biomedical applications and were tested against E. coli as an exemplar of activity. The antimicrobial coatings were very robust under adverse conditions (pH 3 and 10), inhibited the growth of E. coli on their surfaces, and could be used many times with retained activity. Results from a combined spectroscopic (FTIR) and microscopic study (AFM) suggest that the action of these novel particles is through the combined action of cefaclor inhibiting the synthesis of the peptidoglycan layer and gold nanoparticles generating ``holes'' in bacterial cell walls thereby increasing the permeability of the cell wall, resulting in the leakage of cell contents and eventually cell death.